Perpaus osagarri izenlagunak: tradizioa (I) - Alberdi, Xabier; García, Julio; Ugarteburu, Iñaki (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2000)
This article is the first part -"Perpaus osagarri izenlagunak: tradizioa (I)"- of a wider study on the use of adnominal sentences throughout the Basque literary tradition (data obtained from the spoliation of the corpus of the Basque General Dictionary - Orotariko Euskal Hiztegia). The first chapter of this article summarises the classification and presentation of completive adnominal Basque sentences, such as has been exposed by the Academy of the Basque Language in its grammar manual (Euskal Gramatika: Lehen Urratsak - V. Mendeko Perpausak-l, also known as EGLU V). Then the second chapter offers an exhaustive description, as well as abundant examples of the structures that have been used in written tradition with 39 substantives susceptible of phrase complementation (agindu, damu, duda, entzuera, erabaki, errezelo, esperantza, froga, galdera, ideia, etab.).